Machinability analysis of multi walled carbon nanotubes filled alumina composites in wire electrical discharge machining process. Issue 9 (August 2017) - Singh, Meinam Annebushan; Sarma, Deba Kumar; Hanzel, Ondrej; Sedláček, Jaroslav; Šajgalík, Pavol
Abstract: The approach of machining ceramics with electrical discharge machining process is a great challenge till date due to its low electrical conductivity. Machining is made possible by reinforcing with a conductive phase which increases the overall electrical conductivity. Present work focuses on machining of multi walled carbon nanotubes filled alumina composites. Samples with concentrations ranging from 2.5 to 12.5 vol.% are considered for machining. At lower concentration of 2.5 vol.%, effective machining is not possible. Wire lag phenomena is observed during machining at 5 vol.% sample concentration. Proper machinability is observed with concentration of 7.5 vol.% or more. Also, long micro-cracks are obtained during machining that leads to the workpiece breakage. Spalling effect is observed as the most dominating material removal mechanism. A comparison between alumina composites and conducting metallic alloys were carried out for surface characteristics.